An Atmospheric Constraint on the Seasonal Air‐Sea Exchange of Oxygen and Heat in the Extratropics. Issue 8 (18th August 2021) - Morgan, Eric J.; Manizza, Manfredi; Keeling, Ralph F.; Resplandy, Laure; Mikaloff‐Fletcher, Sara E.; Nevison, Cynthia D.; Jin, Yuming; Bent, Jonathan D.; Aumont, Olivier; Doney, Scott C.; Dunne, John P.; John, Jasmin; et al.
Abstract: The air‐sea exchange of oxygen (O2 ) is driven by changes in solubility, biological activity, and circulation. The total air‐sea exchange of O2 has been shown to be closely related to the air‐sea exchange of heat on seasonal timescales, with the ratio of the seasonal flux of O2 to heat varying with latitude, being higher in the extratropics and lower in the subtropics. This O2 /heat ratio is both a fundamental biogeochemical property of air‐sea exchange and a convenient metric for testing earth system models. Current estimates of the O2 /heat flux ratio rely on sparse observations of dissolved O2, leaving it fairly unconstrained. From a model ensemble we show that the ratio of the seasonal amplitude of two atmospheric tracers, atmospheric potential oxygen (APO) and the argon‐to‐nitrogen ratio (Ar/O2 ), exhibits a close relationship to the O2 /heat ratio of the extratropics (40– 70 ° ). The amplitude ratio, A A P O / A A r N 2, is relatively constant within the extratropics of each hemisphere due to the zonal mixing of the atmosphere. A A P O / A A r N 2 is not sensitive to atmospheric transport, as most of the observed spatial variability in the seasonal amplitude of δ APO is compensated by similar variations in δ (Ar/ N 2 ). From the relationship between O 2 /heat and A A P O / A A r N 2 in the model ensemble, we determine that the atmospheric observations suggest hemispherically distinct O 2 /heat flux ratios of 3.3 ± 0.3 and 4.7 ± 0.8 nmol J − 1 between 40 and 70 ° in the Northern and Southern Hemispheres respectively, providing a useful constraint for O 2 and heat air‐sea fluxes in earth system models and observation‐based data products. Plain Language Summary: Typically, the surface of the ocean releases oxygen to the atmosphere during summer and takes it up during winter. This cycle is driven by circulation, biology (photosynthesis and respiration), and the seasonal cycle in water temperature, which changes the solubility of oxygen in surface water. We have used measurements of two atmospheric tracers, one which tracks oxygen and one which tracks heat, to estimate the amount of oxygen taken up or released by a change in ocean heat content. By looking at ocean models and atmospheric observations of the two atmospheric tracers, we find that the oxygen exchange between the ocean and atmosphere in the Southern Hemisphere is more responsive to changes in heat content than in the Northern Hemisphere. These hemispheric metrics are useful tests of how ocean models simulate some biological and physical processes. Key Points: Atmospheric O2 and Ar can constrain the hemispheric air‐sea oxygen to heat flux ratio This constraint is insensitive to uncertainties in atmospheric transport It is also a simple metric for testing ocean biogeochemical models